Physical exercise at the crossroad between muscle wasting and the immune system: implications for lung cancer cachexia - Francesco Cortiula; Lizza E.L. Hendriks; Wouter R.P.H. van deWorp; Annemie M.W.J. Schols; Rianne D.W. Vaes; Ramon C.J. Langen; Dirk De Ruysscher (Wiley, 2022)
Abstract Cachexia is a syndrome characterized by involuntary weight loss and wasting of skeletal muscle mass. It is associated with worse overall survival and quality of life. The cancer‐induced systemic inflammation and the consequent host derived catabolic stimuli, trigger cachexia by inhibiting muscle protein synthesis and enhancing muscle catabolism. The muscle itself may further promote chronic inflammation, introducing a vicious catabolic circle. Nutritional support alone plays a limited role in the treatment of cancer cachexia and should be combined with other interventions. Physical exercise lowers systemic inflammation and promotes muscle anabolism. It also attenuates the age‐related physical decline in elderly and it might counteract the muscle wasting induced by the cancer cachexia syndrome. This review describes how cancer‐induced systemic inflammation promotes muscle wasting and whether physical exercise may represent a suitable treatment for cancer‐induced cachexia, particularly in patients with non‐small cell lung cancer. We summarized pre‐clinical and clinical studies investigating whether physical exercise would improve muscle performance and whether this improvement would translate in a clinically meaningful benefit for patients with cancer, in terms of survival and quality of life. Moreover, this review describes the results of studies investigating the interplay between physical exercise and the immune system, including the role of the intestinal microbiota.